2020
DOI: 10.18203/2319-2003.ijbcp20202950
|View full text |Cite
|
Sign up to set email alerts
|

Study on antibiotic use among geriatric patients based on anatomical therapeutic classification or defined daily dose methodology and world health organization-essential medicine list access, watch and reserve concept in tertiary care hospital of South India

Abstract: Background: Geriatric patients are more vulnerable to infections and need special consideration on antibiotic use. Resistance to antibiotics among infectious bacteria has developed within a short span. There is a direct correlation between the consumption of antibiotics and the development of resistance. And surprisingly very few literatures were available on antibiotic consumption in geriatric population using defined daily dose (DDD) concept which paved the idea to conduct this study.Methods: A prospective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…While, the most frequently prescribed individual antibiotics were meropenem ceftriaxone, and levofloxacin representing 14%, 14%, and 13% respectively of the total antibiotic prescriptions. This finding correlates with a previous prospective observational study including an analysis of 206 prescriptions of geriatric patients revealing that cephalosporins were the most commonly consumed antibiotics (33.2%), specifically cefotaxime (14.6%) and ceftriaxone (12.6%) [1]. This finding supports the documented frequent empirical prescribing of broadspectrum antibiotics, which have a high potential to develop AMR.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While, the most frequently prescribed individual antibiotics were meropenem ceftriaxone, and levofloxacin representing 14%, 14%, and 13% respectively of the total antibiotic prescriptions. This finding correlates with a previous prospective observational study including an analysis of 206 prescriptions of geriatric patients revealing that cephalosporins were the most commonly consumed antibiotics (33.2%), specifically cefotaxime (14.6%) and ceftriaxone (12.6%) [1]. This finding supports the documented frequent empirical prescribing of broadspectrum antibiotics, which have a high potential to develop AMR.…”
Section: Discussionsupporting
confidence: 89%
“…Geriatric patients are more liable to various infections that necessitate particular attention to antibiotics consumption [1]. Antibiotics are frequently utilized to treat infections, but unfortunately, they are increasingly less effective because of the ongoing antimicrobial resistance (AMR) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Senthilkumar et al reported 53.8% of empirical antibiotic use in a tertiary care hospital in India, among geriatric patients admitted between November 2018 and April 2019, with two thirds not having bacteriological investigations. 11 Moreover, 54.4% of the prescribed antibiotics were from WHO Watch category including cefotaxime and ceftriaxone, which goes against WHO stewardship guidance. The WHO in 2017 created the AWaRe (Access, Watch and Reserve) classification for antibiotics to prevent inappropriate use and restricting the newer class for resistant infections and recommends less than 40% of antibiotic usage to be from Watch and Reserve categories.…”
Section: Challenges To Healthcare Workersmentioning
confidence: 99%
“…Only few Indian studies have focused on the pattern and amount of antibiotic use as well as on the level of adherence to antibiotic usage guidelines in various hospital wards to improve prescribing behavior and control irrational use of antibiotics. 5,6 Hence, the aim of this study was to assess antibiotic consumption in our hospital on the basis of volume using DDD and ranking antibiotic usage according to DU90%. The proportion of antibiotics prescribed according to the WHO AWaRe classification and compliance to hospital antibiotic policy were also determined.…”
Section: Introductionmentioning
confidence: 99%